Comparative study on regulatory requirements on corporate social responsibility in Australia and Thailand - Pornchai Wisuttisak (2018)
© 2016 Inderscience Enterprises Ltd. This paper studies regulatory requirements in Australia and Thailand with regard to corporate social responsibility (CSR). The paper presents the general background of CSR in both countries and focus on regulatory obligation which amount to CSR in Australia and Thailand. The paper found that based on regulatory requirements and voluntary basis, CSR in Australia is better developed than Thailand. Australia seems to have more regulations which help facilitate the practices of CSR in businesses. However, the paper also points out that there are similarities between Australia and Thailand regarding CSR. CSR both in Australia is derived from spiritual and philosophical underpinnings. Also another similarity point is that there are limited regulations that can help stimulate the implementation of CSR in companies both in Australia and Thailand. Thus, the paper concludes with a recommendation on regulatory development to CSR in Australia and Thailand.